Measurement error analysis for the determination of dopamine D(2) receptor occupancy using the agonist radioligand [(11)C]MNPA - Shidahara, Miho (Nature Publishing Group, 2010)
The purpose of this study is to investigate errors in quantitative analysis for estimating dopamine D(2) receptor occupancy of antipsychotics with agonist radioligand [(11)C]MNPA by numerical simulation, with particular attention to the validity of a quantitative approach based on the use of a reference region. Synthetic data were validated using clinical data combined with a bootstrap approach. Time–activity curves (TACs) of [(11)C]MNPA were simulated, and the reliability of binding potential (BP(ND)) and occupancy estimated by nonlinear least square (NLS) fitting and a simplified reference tissue model (SRTM) were investigated for various noise levels and scan durations. In the human positron emission tomography (PET) study with and without antipsychotic, risperidone, the uncertainty of BP(ND) and occupancy estimated by SRTM was investigated using resampled TACs based on bootstrap approach with weighted residual errors of fitting. For both NLS and SRTM, it was possible to have <3% of bias in occupancy estimates of [(11)C]MNPA by 60 mins. However, shortened scan duration degrades the quantification of very small binding potentials, especially in case of SRTM. Observations were replicated on the clinical data. Results showed that dopamine D(2) receptor occupancy by antipsychotics can be estimated precisely in region of interest analysis by SRTM with a longer than 60-min [(11)C]MNPA PET scan duration.